Developmental toxicity of Clerodendrum cyrtophyllum turcz ethanol extract in zebrafish embryo. (1st March 2021) - Nguyen, Thu Hang; Nguyen, Phuc-Dam; Quetin-Leclercq, Joëlle; Muller, Marc; Ly Huong, Duong Thi; Pham, Hai The; Kestemont, Patrick
Abstract: Ethnopharmacological relevance: Clerodendrum cyrtophyllum Turcz has been used in traditional medicine for the treatment of various diseases. In spite of its therapeutic applications, research on its toxicity and teratogenicity is still limited. Aim of the study: The study aimed to investigate the developmental toxicity of the ethanol extract of C. cyrtophyllum (EE) in zebrafish embryo model. Material and methods: Major compounds from crude ethanol extract of Clerodendron cyrtophyllum Turcz leaves were determined using HPLC-DAD-Orbitrap-MS analysis . The developmental toxicity of EE were investigated using zebrafish embryo model. Zebrafish embryos at 6 h post-fertilization (hpf) were treated with EE at different concentrations. Egg coagulation, mortality, hatching, yolk sac edema, pericardial edema and teratogenicity were recorded each day for during a 5-day exposure. At time point 120 hpf, body length, pericardial area, heartbeat and yolk sac area were assessed. In order to elucidate molecular mechanisms for the developmental toxicity of EE, we further evaluated the effects of the EE on the expression of genes involved on signaling pathways affecting fish embryo's development such as heart development ( gata5, myl7, myh6, has2, hand2, nkx 2.5 ), oxidative stress ( cat, sod1, gpx4, gstp2 ), wnt pathway (β- catenin, wnt3a, wnt5, wnt8a, wnt11 ), or cell apoptosis ( p53, bax, bcl2, casp3, casp8, casp9, apaf-1, gadd4 5bb ) using qRT-PCR analysis. Results: Our results demonstrated that three major components including acteoside, cirsilineol and cirsilineol-4'- O - β -D-glucopyranoside were identified from EE. EE exposure during 6–96 h post-fertilization (hpf) at doses ranging from 80 to 200 μg/mL increased embryo mortality and reduced hatching rate. EE exposure at 20 and 40 μg/mL until 72–120 hpf induced a series of malformations, including yolk sac edema, pericardial edema, spine deformation, shorter body length. Based on two prediction models using a teratogenic index (TI), a 25% lethality concentration (LD25) and the no observed-adverse-effect level (NOAEL), EE is considered as teratogenic for zebrafish embryos with TI (LC50/EC50) and LD25/NOAEC values at 96 hpf reaching 3.87 and 15.73 respectively. The mRNA expression levels of p53, casp8, bax/bcl2, gstp2, nkx2.5, wnt3a, wnt11, gadd4 5bb and gata5 were significantly upregulated by EE exposure at 20 and 40 μg/mL while the expression of wnt5, hand2 and bcl2 were downregulated. Conclusions: These results provide evidence for toxicity effects of EE to embryo stages and provide an insight into the potential toxicity mechanisms on embryonic development. Graphical abstract: Image 1